Relevance of a sprint interval swim training set to the 100-meter freestyle event based on blood lactate and kinematic variables - Terzi, E.; Skari, A.; Nikolaidis, S.; Papadimitriou, K.; Kabasakalis, A.; Mougios, V. (Journal of Human Kinetics, 2021)
Sprint interval training (SIT) sets are commonly used by coaches in the training routine of swimmers competing in short-distance events; however, data regarding their relevance to competitive events are scarce. The aim of this study was to examine whether performance variables differed or correlated between a 4 × 50-m maximal swimming set (with a work-to-rest ratio of 1:4) and the 100-m freestyle event. Eleven male and 16 female competitive swimmers aged 16.1 ± 1.1 years participated in the study. All swimmers trained at least six times a week and had training experience of more than 4 years. They completed the two freestyle tests on different days, in random and counterbalanced order. In each test, speed, blood lactate, stroke rate (SR), and stroke index (SI) were measured. Speed, blood lactate, and SR were higher at the 4 × 50 m compared to the 100 m and were positively correlated between tests (p < 0.001). The SI did not differ significantly, but was positively correlated between tests. Males were faster and had a higher SI than females, but genders did not differ in lactate. Since performance variables were better in the SIT set and correlated with those in the 100-m bout, we suggest that the 4 × 50-m set can be used to improve performance in the 100-m freestyle event. Moreover, this set can help coaches identify which swimmers will swim fastest in the event.